Toward enhanced photocatalytic activity of graphite carbon nitride through rational design of noble metal-free dual cocatalysts. Issue 25 (22nd June 2020) - Qin, Ling-Zhi; Lin, Ye-Zhan; Dou, Yi-Chuan; Yang, Yi-Jin; Li, Kui; Li, Tao; Liu, Fu-Tian
Abstract : The g-C3 N4 -MoS2 -M(OH) x ternary heterostructures were designed and fabricated for the first time. Abstract : The g-C3 N4 -MoS2 -M(OH) x ternary heterostructures were designed and fabricated for the first time. The embedding of noble-metal-free MoS2 -M(OH) x dual cocatalysts over g-C3 N4 nanosheets led to obvious synergistic effect for improving the transport as well as utilization efficiency of photo-generated charge carriers. Consequently, the optimal ternary heterostructure (g-C3 N4 -MoS2 -Ni(OH)2 ) exhibited photocatalytic hydrogen production activity 4.5 times larger than the sum of the photocatalytic HER activity of g-C3 N4 -MoS2 and g-C3 N4 -Ni(OH)2 . More significantly, even in the absence of the sacrificial agent, the g-C3 N4 -MoS2 -Ni(OH)2 ternary heterostructure exhibited a photocatalytic HER activity of 0.3 mmol h −1 g −1 with considerable H2 O2 production under UV-visible light.